Industrial Training Report: Perpustakaan Tengku Anis UiTM Kelantan / Nur Athirah Abdullah - Abdullah, Nur Athirah (Faculty of Information Management, 2018)
In this report, its provides a comprehensive description about the practical training which are being carried out at Perpustakaan Tengku Anis, UiTM Machang Kelantan for a 5 months period. There are 4 chapter's contains introduction to UiTM Machang and Perpustakaan Tengku Anis, differences of roles and job scopes that carried out by 9 departments at Perpustakaan Tengku Anis, the activities that are being carried out during the practical training and special project managed and lastly, knowledge and lesson gained during the time period of training. The first chapter, it's introduced the background of UiTM Machang and PTA also. While the second chapter, it is the explanation of departments in PTA which Administration, Customer Service, Cataloguing, Acquisition, Journal, Archive, Conservation, Information Services and Information Technology. Third chapter was about training activities during training on department by department and last chapter was about conclusion includes knowledge and lesson learned along the outcomes after practical training.